Efficacy and safety of premedication with single dose of oral pregabalin in children with dental anxiety: A randomized double-blind placebo-controlled crossover clinical trial - Tahereh Eskandarian; Hamidreza Eftekharian; Rojin Soleymanzade (Wolters Kluwer Medknow Publications, 2015)
Background: Dental anxiety is a relatively frequent problem that can lead to more serious problems such as a child entering a vicious cycle as he/she becomes reluctant to accept the required dental treatments. The aim of this randomized double-blind clinical trial study was to evaluate the anxiolytic and sedative effect of pregabalin in children. Materials and Methods: Twenty-five children were randomized to a double-blind placebo-controlled crossover clinical trial. Two visits were scheduled for each patient. At the first visit, 75 mg pregabalin or placebo was given randomly, and the alternative was administered at the next visit. Anxiolytic and sedative effects were measured using the visual analogue scale. The child's behavior was rated with the Frankl behavioral rating scale and the sedation level during the dental procedure was scored using the Ramsay sedation scale. The unpaired, two-tailed Student's t-test was used to compare the mean changes of visual analog scale (VAS) for anxiety in the pregabalin group with that of the placebo group. A repeated measures MANOVA model was used to detect differences in sedation level in the pregabalin and placebo groups regarding the interaction of 3-time measurements; sub-group analysis was performed using Student's t-test. The Mann-Whitney U-test was used to analyze the nonparametric data of the Frankl and Ramsay scales. A P < 0.05 was considered significant. Results: The reduction of the VAS-anxiety score from 2 h post-dose was statistically significant in the pregabalin group. From 2 h to 4 h post-dose, the VAS-sedation score increased significantly in the pregabalin group. The child's behavior rating was not significantly different between the groups. The number of "successful" treatment visits was higher in the pregabalin group compared to the placebo group. Conclusion: Significant anxiolytic and sedative effects can be anticipated 2 h after oral administration of pregabalin without serious side effects.